HUBUNGAN HENDAYA KOGNITIF NON DEMENSIA DENGAN KENDALI GLIKEMIK PADA PENYANDANG DIABETES MELITUS TIPE 2 - M. Kurniawan*, Adre Mayza*, Salim Harris*, Budiman** (Neurona Majalah Kedokteran Neuro Sains, 2010)
INTRODUCTION PATIENTS WITH TYPE 2 DIABETES MELLITUS HAVE BEEN FOUND TO HAVE COGNITIVE DYSFUNCTION THAT CAN BE ATTRIBUTED TO THEIR DISEASE LONGITUDINAL STUDIES HAVE SHOWN THE ASSOCIATION OF TYPE 2 DIABETES MELLITUS WITH BOTH DEMENTIA AND MILD COGNITIVE IMPAIRMENT ONE PROPOSED FACTOR WHICH CONTRIBUTE TO THE PATHOPHYSIOLOGY OF COGNITIVE DYSFUNCTION IN PATIENTS WITH TYPE 2 DIABETES MELLITUS IS CHRONIC HYPERGLYCEMIA THROUGH ENDOTHELIAL DYSFUNCTION AND NEUROTRANSMITTER DISTURBANCE MECHANISMS